2018
DOI: 10.1136/bmjopen-2017-018838
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors of inhospital death in elderly patients: a time-to-event analysis of a cohort study in Martinique (French West Indies)

Abstract: ObjectiveThe primary objective was to identify predictive factors of inhospital death in a population of patients aged 65 years or older hospitalised with Chikungunya virus (CHIKV) infection. The secondary aim was to develop and validate a predictive score for inhospital death based on the predictors identified.DesignLongitudinal retrospective study from January to December 2014.SettingUniversity Hospital of Martinique.ParticipantsPatients aged ≥65 years, admitted to any clinical ward and who underwent reverse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…7 Another recent study, with patients admitted in an intensive care unit because of CHIKV infection in India, evidenced that disease severity was mainly associated with advanced age and the presence of underlying comorbidities, and risk factors for death were high acute physiology and chronic health evaluation (APACHE) II score at admission and dialysis requirement, 24 which also evidences that kidney injury increases mortality. Cardiovascular disorders, respiratory secondary infections, sensoriomotor deficit, absence of musculoskeletal pain, history of alcoholism, digestive symptoms, and presence of confusion/ delirium were factors independently associated with death among elderly patients admitted with CHIKV infection in a university hospital in Martinique 25 and reinforce the fact that comorbidities increase the infection severity and the risk of death.…”
Section: Discussionmentioning
confidence: 63%
“…7 Another recent study, with patients admitted in an intensive care unit because of CHIKV infection in India, evidenced that disease severity was mainly associated with advanced age and the presence of underlying comorbidities, and risk factors for death were high acute physiology and chronic health evaluation (APACHE) II score at admission and dialysis requirement, 24 which also evidences that kidney injury increases mortality. Cardiovascular disorders, respiratory secondary infections, sensoriomotor deficit, absence of musculoskeletal pain, history of alcoholism, digestive symptoms, and presence of confusion/ delirium were factors independently associated with death among elderly patients admitted with CHIKV infection in a university hospital in Martinique 25 and reinforce the fact that comorbidities increase the infection severity and the risk of death.…”
Section: Discussionmentioning
confidence: 63%
“…The only available data concern short-term mortality [6,29] in the general population, or in-hospital mortality in the general population [7,10] or in elderly patients [13]. We reported that 9.1% of patients aged 65 years or older hospitalised with CVI died during the hospital stay [13]. Economopoulou et al [10] reported that presentation of an atypical or severe form of CVI was an independent predictor of death at the acute phase.…”
Section: Discussionmentioning
confidence: 88%
“…Data are lacking in the literature concerning mortality in the medium or long term after CVI, thus precluding comparison of our results with other studies. The only available data concern short‐term mortality in the general population, or in‐hospital mortality in the general population or in elderly patients . We reported that 9.1% of patients aged 65 years or older hospitalised with CVI died during the hospital stay .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study among patients aged 65 years and older reported a mortality of 9.1% in this group, and the predictors of death identified were the presence of cardiovascular, respiratory, neurological, or digestive disorders, and a history of alcoholism. 8 Therefore, these should all be considered as signs of disease severity in this population and not signs of atypical presentation. Dorléans et al 1 reported that there were 74 deaths in their study, but it would have been interesting to specify the distribution of these deaths according to the clinical forms they described.…”
mentioning
confidence: 99%